Longarm and the whiskey runners - Evans, Tabor (Evans, Tabor. Longarm ;, 2014)
"One good lawman has already been murdered in pursuit of Missouri moonshiners who could care less if their rotgut leaves a person blind--or even dead. Now it's Deputy U.S. Marshal Custis Long's turn to search out their stills and make sure these moonshiners don't see the light of day. But as Longarm explores the back country, he learns there's far more at stake than selling bad hooch to the locals. Intoxicated by greed, one man is behind an ambitious whiskey-running operation to sell firewater--and firearms--to the Indians. It's up to Longarm to give this liquor-lugging lunatic a shot and a chaser of a little something called justice"--Page [4] of cover.